Social provisioning as a starting point for feminist economics - Power, Marilyn (Feminist Economics, 2004)
The past decade has seen a proliferation of writing by feminist economists. Feminist economists are not identified with one particular economic paradigm, yet some common methodological points seem to be emerging. I propose making these starting points more explicit so that they can be examined, critiqued, and built upon. I use the term “social provisioning” to describe this emerging methodology. Its five main components are: incorporation of caring and unpaid labor as fundamental economic activities; use of well-being as a measure of economic success; analysis of economic, political, and social processes and power relations; inclusion of ethical goals and values as an intrinsic part of the analysis; and interrogation of differences by class, race-ethnicity, and other factors. The paper then provides brief illustrations of the use of this methodology in analyses of US welfare reform, gender and development, and feminist ecological economics.
Keywords: OFDIG; approches et analyses; discipline; droits des femmes*; genre; identités LGBTQIA2+; méthodologie; point de vue situé; ressource en ligne; sciences de la gestion; thématiques; économie